2017
DOI: 10.1371/journal.pone.0179594
|View full text |Cite
|
Sign up to set email alerts
|

Living in the waterfalls: A new species of Trichomycterus (Siluriformes: Trichomycteridae) from Tabay stream, Misiones, Argentina

Abstract: A new species assigned to the genus Trichomycterus from the area of the waterfalls of Tabay stream, Paraná River basin, Misiones, Argentina, is described. Trichomycterus ytororo sp. nov. is distinguished from all other species in the genus by the presence of 31–35 dorsal procurrent caudal-fin rays and the combination of some external characters such as: coloration, number of pectoral–fin rays and pores of the laterosensory canals. The new taxon belongs to a presumably monophyletic group of species composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Subsequently, Datovo & Bockmann 29 provided evidence from the head musculature supporting a clade consisting of C. davisi and C. stawiarski. Datovo et al 78 included C. perkos in that group based on the shared presence of a high number of branchiostegal rays and, more recently, Terán et al 79 found morphological support to include in that group also their newly described C. ytororo. Katz et al 31 diagnosed Cambeva based on a combination of plesiomorphic or general character states and some derived characters uniquely shared by Cambeva and Scleronema.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Datovo & Bockmann 29 provided evidence from the head musculature supporting a clade consisting of C. davisi and C. stawiarski. Datovo et al 78 included C. perkos in that group based on the shared presence of a high number of branchiostegal rays and, more recently, Terán et al 79 found morphological support to include in that group also their newly described C. ytororo. Katz et al 31 diagnosed Cambeva based on a combination of plesiomorphic or general character states and some derived characters uniquely shared by Cambeva and Scleronema.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, five pelvic-less trichomycterines have been recorded from the Argentinean Andes (Fernández and Liotta 2016), as well as two species lacking pelvic fin being described from south-eastern and southern Brazil (Ferrer and Malabarba 2011;Ochoa et al 2017a). These Brazilian species are presently placed in Cambeva Katz, Barbosa, Mattos & Costa, 2018, a genus comprising 25 valid species endemic to south-eastern and southern Brazil (Katz et al 2018;dos Reis et al 2019), as well as a single species from north-eastern Argentina (Terán et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, this group has been the subject of constant redefinitions (Barbosa & Costa, ; Bockmann & Sazima, ) that have deeply altered its taxonomic composition each time, thus raising concerns about its actual monophyletic nature (Ferrer & Malabarba, ). Other efforts recognizing subgroups of species within Trichomycterus followed (Bizerril, ; Fernández & Vari, ; Bockmann et al ., ; Wosiacki & Garavello, ; Wosiacki, ; Alencar & Costa, ; Fernández & Osinaga, ; Fernández & Miranda, ; Lima et al ., ; Wosiacki & de Pinna, , ; Barbosa & Costa, for T. itatiayae species complex; Barbosa & Costa, for T. travassosi species complex, 2012b; Datovo et al ., ; Fernández & Vari, ; Katz et al ., ; Katz & Barbosa, ; Terán et al ., for T. stawiarski group). Further complicating the recognition of putative monophyletic groups within Trichomycterus , several authors have discussed the morphological evidence suggesting closer phylogenetic relationships of some Trichomycterus species with other trichomycterine genera (DoNascimiento et al ., ; Fernández & Quispe Chuquihuamaní, ; Fernández & Schaefer, ; Mesa et al ., ), and even with other trichomycterid subfamilies (de Pinna, ).…”
Section: Discussionmentioning
confidence: 99%